Single high-dose vitamin D supplementation impacts ultramarathon-induced changes in serum levels of bone turnover markers: a double-blind randomized controlled trial - Stankiewicz, Błażej; Kochanowicz, Andrzej; Brzezińska, Paulina; Niespodziński, Bartłomiej; Reczkowicz, Joanna; Waldziński, Tomasz; Kowalik, Tomasz; Piskorska, Elżbieta; Wędrowska, Ewelina; Antosiewicz, Jędrzej; Mieszkowski, Jan (Journal of the International Society of Sports Nutrition, 2025)
BACKGROUND: Recent studies indicate a protective role of vitamin D supplementation against sports performance-induced dysregulation of body homeostasis. However, the effects of a single high dose of vitamin D on changes in bone formation and resorption markers due to ultramarathon running have yet to be explored. This study aimed to analyze the effect of a single high-dose vitamin D supplementation on serum levels of bone turnover markers after a mountain ultramarathon run. METHODS: In this clinical trial (reg. number NCT03417700), 35 semiprofessional male ultramarathon runners were assigned into two groups: supplemented group, administered a single high dose of vitamin D3 (cholecalciferol, 150,000 IU) in vegetable oil 24 h before the start of the run (n = 16), and placebo group (n = 19), administered placebo solution 24 h before the start of the run. Blood samples were collected for analysis at three timepoints: 24 h before, immediately after, and 24 h after the run. RESULTS: Serum 25(OH)D3 level significantly increased (p ≤ 0.05.) after the ultramarathon in both groups. The increase was more pronounced in the supplemented population, especially 24 h after the run (147.01% vs 84.71%). According to post-hoc and other analyses, the levels of N-terminal propeptides of type I collagen, a PINP marker, were increased immediately after the run. The increase was significantly higher in the supplemented group than in the control group. CTX, PTH, sclerostin, and procalcitonin levels were significantly higher 24 h after the run in the control group. CONCLUSIONS: The observed attenuation of post-exercise bone resorption and enhancement of bone formation suggest that vitamin D supplementation may modulate bone metabolism in response to extreme physical exertion, potentially through effects on calcium - PTH homeostasis.
Keywords: Collagen Type I; CTX; Male; sclerostin; biologické markery; cholekalciferol; maratonský běh; prokolagen; Biomarkers; parathormon; kolagen typu I; PINP; Parathyroid Hormone; Adult; Marathon Running; dospělí; mužské pohlaví; vitamin D; potravní doplňky; Dietary Supplements; Ultramarathon; dvojitá slepá metoda; peptidové fragmenty; Bone Remodeling; běh; lidé; Humans; remodelace kosti; Cholecalciferol; Peptides; Running; peptidy; Calcifediol; kalcifediol; Double-Blind Method; Vitamin D; Procollagen; Peptide Fragments; skeletal muscle damage; lidé středního věku; Middle Aged